2017
DOI: 10.1093/carcin/bgx136
|View full text |Cite
|
Sign up to set email alerts
|

A novel bioactive derivative of eicosapentaenoic acid (EPA) suppresses intestinal tumor development in ApcΔ14/+ mice

Abstract: Familial adenomatous polyposis (FAP) is a genetic disorder characterized by the development of hundreds of polyps throughout the colon. Without prophylactic colectomy, most individuals with FAP develop colorectal cancer at an early age. Treatment with EPA in the free fatty acid form (EPA-FFA) has been shown to reduce polyp burden in FAP patients. Since high-purity EPA-FFA is subject to rapid oxidation, a stable form of EPA compound has been developed in the form of magnesium l-lysinate bis-eicosapentaenoate (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 43 publications
(63 reference statements)
3
16
0
Order By: Relevance
“…Another lipid-related metabolite, HDoHE, was also negatively correlated with tumor weight, in line with a previous study that revealed a higher level of HDoHE was associated with smaller CRC tumors in mice, owing to the anti-inflammatory properties of HDoHE [39]. These findings indicate that ZEA may aggravate tumor growth by interfering with systemic metabolism.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Another lipid-related metabolite, HDoHE, was also negatively correlated with tumor weight, in line with a previous study that revealed a higher level of HDoHE was associated with smaller CRC tumors in mice, owing to the anti-inflammatory properties of HDoHE [39]. These findings indicate that ZEA may aggravate tumor growth by interfering with systemic metabolism.…”
Section: Discussionsupporting
confidence: 90%
“…We observed that serum hydroxyeicosatetraenoic acids (HETE) level was lower in the ZEA group, potentially leading to defects in PPARγ activation which is responsible for apoptosis in CRC [46]. Another lipid-related metabolite, hydroxydocosahexaenoic acid (HDoHE), was also found to be negatively correlated with tumor weight, in line with a previous study that revealed that a higher level of HDoHE was associated with smaller CRC tumors in mice due to the anti-inflammatory property of HDoHE [47]. These results suggested that ZEA could possibly hinder the production of anti-inflammatory metabolites, leading to aggravated tumor growth.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, only after the encapsulation, DHA was efficiently retroconverted into EPA. The increased efficiency of cancer cells to incorporate EPA after administration of the SLN containing either its precursor LNA or its metabolic product DHA seems to be of great interest, since several reports have demonstrated the ability of EPA or its derivatives to exert a protective action in animals and patients at high risk for CRC [ 56 , 57 , 58 , 59 ]. Particularly, the possibility of efficiently increasing (by almost three folds) the content of EPA in colonic cells by administering LNA-RV-SLN seems particularly noteworthy, since the direct intake of EPA from fish or after its purification is much less sustainable and affordable than the use of LNA for encapsulation, being this metabolic precursor of EPA largely found in vegetables and seeds.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that the encapsulation of either DHA or ALA into RV-based SLN could also markedly increase the CRC content of EPA, which, according to several recent reports, seems to protect against CRC risk better than all the other main ω-3 PUFAs. [106][107][108] The more efficient conversion of SLN-encapsulated ALA is particularly interesting when considering that ALA is present at high levels in a variety of seeds and vegetables, and its increased intake could be achieved more easily and in a more sustainable way compared to an increased consumption of EPA itself.…”
mentioning
confidence: 99%